Liberal nationalism in Central Europe - Auer, Stefan, 1964- (RoutledgeCurzon contemporary Russia and Eastern Europe series, 2004)
After the collapse of communism there was a widespread fear that nationalism would pose a serious threat to the development of liberal democracy in the countries of central Europe. This book examines the role of nationalism in post-communist development in central Europe, focusing in particular on Poland, the Czech Republic and Slovakia. It argues that a certain type of nationalism, that is liberal nationalism, has positively influenced the process of postcommunist transition towards the emerging liberal democratic order.